Examining the psychometric properties of the achievement goals questionnaire among nigerian preservice mathematics and science teachers - Awofala, A.O.A.; Arigbabu, A.A.; Fatade, A.O.; Awofala, A.A. (2013)
The stability of the achievement goal orientation across different contexts has been a source of further research since the new millennium. Through theoretically-driven and empirically-based analyses, this study investigated the psychometric properties of the Elliot and McGregor 22 framework for achievement goal questionnaire within a communal context. Method. Based on classical test theory, the present study attempted to explore the stability of the 22 framework for Achievement Goal Questionnaire (AGQ) using exploratory factor analysis involving the principal components extraction with orthogonal and oblique rotations. Results. Results support the factor structure of the 22 achievement goal framework in the collectivist culture context. Discussion. The present study provides evidence that suggests that achievement goal construct as measured by AGQ, appears to be culturally and contextually invariant thus reinforcing the four-factor model namely mastery-approach, performance-approach, masteryavoidance, and performance-avoidance in domain specific context. Future research should focus on determining the psychometric properties of the 22 achievement goals in Mathematics Education Questionnaire and Science Education Questionnaire using both the classical test theory and modern item response theory to refute or generalise existing results. Education Psychology I+D+i and Editorial EOS(Spain).
KerkoCite.ItemAlsoKnownAs: 10.14204/ejrep.31.13037 4893635:8ADA5GK4 5168324:28XLL9QW
Keywords: Mathematics education; Science education; Teacher knowledge and skills; Teacher motivation; _C:Nigeria; _authorsString:Second; A.B.; _checkedWith:AERD; _research:Quantitative; _type:Peer-reviewed article

Attitudes toward computer, computer anxiety and gender as determinants of pre-service science, technology, and mathematics teachers' computer self-efficacy - A.O.A., Awofala; O.S., Olabiyi; A.A., Awofala; A.A., Arigbabu; A.O., Fatade; Udeani, U.N. (2019)
For Nigeria to attain her Vision 20: 2020, the school curricula must change in line with the development in technology. Teachers should be able to adapt technology into the teaching and learning process. Three non-intellectual elements that affect the degree of integration of technology into teaching and learning are attitude toward computer, computer anxiety and computer self-efficacy. The study investigated attitudes towards computer, computer anxiety and gender as determinants of computer self-efficacy among 2100 pre-service science, technology and mathematics (STM) teachers from the University of Lagos of Nigeria using the quantitative research method within the blueprint of the descriptive survey design. Data collected were analysed using the descriptive statistics of percentages, mean, and standard deviation and inferential statistics of independent samples t-test, Pearson product-moment correlation coefficient and multiple regression analysis. Finding revealed significant correlations between computer attitudes, computer anxiety and computer self-efficacy. Gender differences in attitude toward computer, computer self-efficacy and computer anxiety among pre-service STM teachers were significant. Affective component; perceived control component; perceived usefulness component; behavioural intention component; gender; and computer anxiety made statistically significant contributions to the variance in pre-service STM teachers' computer selfefficacy. The study recommended among others that academic institutions should pay more attention to this computer anxiety and adopt proper ways of reducing the computer anxiety. This will enable positive e-learning experiences to be created for pre-service STM teachers. 2019 Research Group Education and Virtual Learning (GREAV). All rights reserved.
KerkoCite.ItemAlsoKnownAs: 4893635:R2APB7PE 5168324:EVJ5PMQT
Keywords: E-learning; Gender disparities; Higher education; ICT in education; Mathematics education; Science education; Teaching methods; _C:Nigeria; _authorsString:Second; A.B.; _checkedWith:AERD; _research:Quantitative; _type:Peer-reviewed article

Investigating digital distraction among pre-service science, technology, and mathematics teachers in Nigeria - Awofala, A.O.A.; Olabiyi, O.S.; Awofala, A.A.; Ojo, O.T.; Okunuga, R.O. (2020)
Internationally, the proliferation of digital technologies in classrooms has produced digital distractions among digital natives in this 21st century. Thus, it is highly imperative to develop a suitable instrument for assessing and measuring digital distraction among higher education students to enable continuing research and practice. While previous studies had treated and measured digital distraction as a sub-component of a multi-dimensional construct and as a test, the present study through instrumentation survey research, developed and authenticated a standalone digital distraction scale among pre-service science, technology and mathematics (STM) teachers in Nigeria. The instrument is constructed by adopting a multidimensional standpoint of digital distraction around a higher-order modelling method. The pre-service STM teachers were recruited from a culturally varied university student population in Nigeria. The results showed a high level of digital distraction among the pre-service STM teachers in Nigeria and the digital distraction is composed of several connected yet distinctive factors (emotional distraction, digital addiction, and distraction by procrastination), with proof backing up a higher-order structural archetypal. More so, empirical evidence confirmed the measurement invariance of the scale with regards to gender and the consistency of the psychometric properties of the digital distraction scale. Finally, test-retest reliability of the digital distraction scale showed that the scores are not variable over time and that the scale is not sensitive to alterations in the learning milieu. Finally, it is hoped that this tool will be handy for educators interested in isolating pre-service STM teachers at risk of high digital distraction which may cause lack of respect and privation of courtesy for instructors and personal distraction in the classroom. 2020 Research Group Education and Virtual Learning (GREAV). All rights reserved.
KerkoCite.ItemAlsoKnownAs: 10.1344/DER.2020.37.32-48 4893635:LAZSNUUA 5168324:EM4EXRWU
Keywords: ICT in education; Mathematics education; Science education; Teacher capacity; _C:Nigeria; _authorsString:Second; A.B.; _checkedWith:AERD; _research:Quantitative; _type:Peer-reviewed article